Social determinants of exclusive breastfeeding in term infants under the age of 6 months in a Health Center in San Juan de Lurigancho, 2017 - Prado Cuadros, Teresa (2018)
Objective: To establish the social determinants of exclusive breastfeeding in term infants under the age of 6 months in a Health Center in San Juan de Lurigancho, 2017. Materials and Methods: The study was applied, descriptive and considered the non-experimental and transactional design. It was included 100 mothers with children between 0 and 6 months who were attended at the Growth and development Service, and it was obtained a sample of 50 mothers by using the non-probabilistic selection. Data analysis was developed using the SPSS software and results were showed in frequency charts. Results: Most of the mothers who participated in the study are young between 20 and 35 years old, most of the mothers had some difficulty in relation to the abandonment of Breastfeeding with 78%, 68% of mothers referred to have a job, 32% of them referred to have a technical higher education degree, most of the mothers referred to have knowledge about breastfeeding techniques and they got suggestion from health services professionals. Conclusion: Feeding is appropriate, mothers have some difficulty that is in relation to the abandonment of Breastfeeding, most of the mothers have a job and they developed technical studies. Mothers have appropriate information about breastfeeding techniques and they got information from health services professionals.